Effectiveness of home rehabilitation for ischemic stroke - Pakaratee Chaiyawat; Kongkiat Kulkantrakorn; Paskorn Sritipsukho (Neurology International, 2009)
The objective of this study was to develop and examine the effectiveness of an individual home rehabilitation program for patients with ischemic stroke. This was a randomized controlled trial in 60 patients with recent middle cerebral artery infarction. After hospital discharge for acute stroke care, they were randomly assigned to receive either a home rehabilitation program for three months (intervention group) or usual care (control group). We collected outcome data over three months after their discharge from the hospital. The Barthel Index (BI), the Modified Rankin Scale (MRS), the health-related quality-of-life index (EQ-5D), the Hospital Anxiety and Depression score (HADs), and the Thai Mental State Examination (TMSE) were used to analyze the outcomes. In the intervention group, all outcomes were significantly better (p